Effect of Helicobacter pylori infection on 24 hour intragastric acidity in patients with gastritis and duodenal ulcer. Issue 8 (August 1992) - Wagner, S; Gladziwa, U; Haruma, K; Varrentrapp, M; Gebel, M
Abstract : Helicobacter pylori status, gastric histology, and 24 hour acidity were studied in 35 gastritis patients, 21 duodenal ulcer patients, and 14 subjects with normal gastric mucosa. H pylori was identified in 21 of 35 patients with chronic active gastritis and in 19 of 21 duodenal ulcer patients, but in none of those with normal gastric mucosa. Mean scores of activity of gastritis were similar in H pylori positive gastritis and duodenal ulcer patients, but were significantly lower in H pylori negative gastritis patients (2.1 (0.8) and 2.3 (0.9) v 1.4 (0.7); p < 0.01, respectively). Median 24 hour hydrogen ion activity (interquartile range) was 21 (8.9-38.0) mmol/l in normal subjects and 23 (11.2-49.0) mmol/l, 19 (7.1-33.1) mmol/l, 44 (25.1-63.1) mmol/l, and 36 (31.6-39.8) mmol/l respectively in gastritis and duodenal ulcer patients with and without H pylori infection. During all predefined time periods, intragastric acidity was significantly higher in patients with H pylori positive duodenal ulcers compared with gastritis patients and normal subjects. However, there was no significant difference in intragastric acidity between the H pylori positive and negative gastritis patients. These results suggest that most of the subjects with chronic H pylori infection have normal gastric acidity.